Optimization of lng cold energy utilization via power generation, refrigeration, and air separation - Rao, V.V. (Universitas Pendidikan Indonesia, 2020)
Natural gas is conventionally transported in its liquid form or Liquid Natural Gas (LNG). It is then transported using cryo-genic insulated LNG tankers. At receiving terminals, LNG is regasified prior to distributing it through gas distribution sys-tem. Seawater has been used as the heat source, which leads to vast amount of cold energy discarded into the water. This work presents the use of LNG cold energy around Melaka Re-fining Company (MRC). The cold energy is utilized in power generation, propylene refrigeration cycle, and air separation plants. These systems are designed and simulated using a commercial process simulation software. Capital cost (CAPEX) function and revenues of each system are further developed as a function of LNG flowrates. These developed correlations are then used in an optimization problem to seek for the most profitable scenario. The results show that utilizing LNG for air separation unit yields the highest profit compared to power generation and refrigeration plants. Â© 2020 Tim Pengembang Jurnal UPI.